31. AUGMENTATION PLATE AND BONE GRAFTING TO TREAT FEMORAL SHAFT NONUNION INITIALLY FIXED BY CLOSED INTRAMEDULLARY NAILING AND LOCKING - ONE CASE REPORT (Vietnam Journal of Community Medicine, 2024)
Objective: Introduce an effective treatment for the femoral shaft nonunion, after failure of closed intramedullary nailing and locking. Method: Descriptive one - case report of femoral shaft nonunion due to failure of closed intramedullary nailing and locking. Patient was reoperated: debridement of nonunion, cancellous autograft harvested from iliac wing, augmentation plate with 6 screws. No hardware removal of anterior surgery. Results: Postoperative follow-up after 1,3,6 months. Bone healing registered in the end of 3th month.Walking and light running were performable.Hardwares removal was carried out after 30 months. The last follow-up at 33th month (since augmentation plate and bone graft surgery): good bone healing, range of motion (hip, knee,ankle) well recovered. Normal walking, running, sports practices well regained. Harris score was 98/100. Conclusion: Treatment for femoral shaft nonunion due to failure of initially closed intramedullary nailing and locking by debridement, no removal of anterior hardware, cancellous autograft and augmentation plate resumed effective, easy to perform, good reference for orthopaedic practice.
Keywords: Plate augmentation, autogenous cancellous bone graft.